2022
DOI: 10.3897/neobiota.71.79597
|View full text |Cite
|
Sign up to set email alerts
|

A review of invasive species reporting apps for citizen science and opportunities for innovation

Abstract: Smartphone apps have enhanced the potential for monitoring of invasive alien species (IAS) through citizen science. They now have the capacity to massively increase the volume and spatiotemporal coverage of IAS occurrence data accrued in centralised databases. While more reporting apps are developed each year, innovation across diverse functionalities and data management in this field are occurring separately and simultaneously amongst numerous research groups with little attention to trends, priorities and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 65 publications
0
33
0
Order By: Relevance
“…It is imperative to highlight the importance of early monitoring programmes for newly introduced populations. Almost half of the records have been obtained from citizen science platforms, which have become a very useful tool for monitoring the expansion of alien populations (Howard et al, 2022). To facilitate future identifications and studies, we also provide illustrations of the larvae, pupae and adults found in the Iberian Peninsula as well as the signs that allow us to detect a Trachymela infestation.…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative to highlight the importance of early monitoring programmes for newly introduced populations. Almost half of the records have been obtained from citizen science platforms, which have become a very useful tool for monitoring the expansion of alien populations (Howard et al, 2022). To facilitate future identifications and studies, we also provide illustrations of the larvae, pupae and adults found in the Iberian Peninsula as well as the signs that allow us to detect a Trachymela infestation.…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian Hierarchical Models, Section V), and prioritizing volunteer sampling in areas that would contribute most to modelling (Callaghan et al ., 2019). Mobile apps and open online databases (see Section IV) are also an important part of facilitating and enhancing the role of community science in IAS monitoring (Johnson et al ., 2020; Howard et al ., 2022).…”
Section: Ias Occurrence Datamentioning
confidence: 99%
“…Historically, community science mainly involved volunteers assisting professional technicians to collect data in the field, but websites and smartphone applications have opened new avenues for participation (Mazumdar et al ., 2018; Howard et al ., 2022). Digital crowdsourcing allows people to participate virtually in a variety of roles, including as volunteer naturalists, identifying species based on observations (e.g.…”
Section: Ias Occurrence Datamentioning
confidence: 99%
“…If the study species was found, we recorded the number of individuals (timed counts in combination with snapshot counts -methodology described in [43]), collected specimens if possible, and documented the abundance and blooming status of plants following the protocol described by Bila Dubaić et al [43]. This protocol also allowed us to gather data on 'not detected' records for study sites (figure 3): when necessary conditions were met (optimal weather conditions and the sufficient abundance of blooming key floral resources), but no records of M. sculpturalis were obtained [79,[82][83][84][85].…”
Section: Systematic/targeted Researchmentioning
confidence: 99%